2003
DOI: 10.1021/jf030117h
|View full text |Cite
|
Sign up to set email alerts
|

Major Flavonoids in Grape Seeds and Skins:  Antioxidant Capacity of Catechin, Epicatechin, and Gallic Acid

Abstract: Grape seeds and skins are good sources of phytochemicals such as gallic acid, catechin, and epicatechin and are suitable raw materials for the production of antioxidative dietary supplements. The differences in levels of the major monomeric flavanols and phenolic acids in seeds and skins from grapes of Vitis vinifera varieties Merlot and Chardonnay and in seeds from grapes of Vitis rotundifolia variety Muscadine were determined, and the antioxidant activities of these components were assessed. The contribution… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

35
375
5
7

Year Published

2007
2007
2018
2018

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 623 publications
(422 citation statements)
references
References 40 publications
35
375
5
7
Order By: Relevance
“…In addition, soluble tannins are also responsible for the high water-soluble antioxidant properties (Homoki et al, 2016). Phlorizin, chlorogenic acid, and epicatechin, three phenolic compounds accounting for relatively high content in YAP, have been shown antioxidant potentials as well (Cai et al, 2013;Sato et al, 2011;Yilmaz & Toledo, 2004). All the methods used in this study showed a high reducing capacity for YAP, by which the oxyradicals could be scavenged.…”
Section: Antioxidant Activities Of Yapsupporting
confidence: 62%
“…In addition, soluble tannins are also responsible for the high water-soluble antioxidant properties (Homoki et al, 2016). Phlorizin, chlorogenic acid, and epicatechin, three phenolic compounds accounting for relatively high content in YAP, have been shown antioxidant potentials as well (Cai et al, 2013;Sato et al, 2011;Yilmaz & Toledo, 2004). All the methods used in this study showed a high reducing capacity for YAP, by which the oxyradicals could be scavenged.…”
Section: Antioxidant Activities Of Yapsupporting
confidence: 62%
“…The advantage of this disinfection technique is that polyphenols are supposed to be safe for humans because they are edible compounds naturally occurring in fruits, vegetables, nuts, seeds, and flowers. In addition, since those polyphenolic compounds are noteworthy for its antioxidative activity [74,75], they might alleviate the oxidative damage in the tissue after the disinfection treatment. Therefore, it is expected that this disinfection technique is applicable to the fields of medical and food sanitation.…”
Section: Other Hydroxyl Radical Generation Systemsmentioning
confidence: 99%
“…The following list gives an enumeration of all the measures or procedures investigated: Maturity, ripening and time of harvest [63,74,82,99,115,116,176,178,179,188,189,194] 58,112,142,162,181,191,196], differentiation in fractions [114,167,174], peeling [109,142,153,180], special pressing or extraction [2, 64,72,165], enzymatic treatment and maceration [51], irradiation [53,158,175,183], drying [8,102,132,152,159], sensory effects [51], germination [88], browning-blanching and polyphenoloxidase (PPO) activity [124], proveniences [8,12,63,107,110,112,…”
Section: Aspects Of Postharvest Processing and Storage Proceduresmentioning
confidence: 99%